1999
DOI: 10.1089/gte.1999.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Testing of Children for Two X-Linked Diseases: A Retrospective Evaluation of Experience and Satisfaction of Subjects and Their Mothers

Abstract: Carrier testing of children for inherited disease that will not affect the health of the children themselves but of their future children is generally regarded as problematic. In this retrospective study, we determined how young women had experienced genetic carrier testing when they were children. The families of 66 young females who had been tested for carriership during childhood between 1984 and 1988, were approached. Of them, 23 young females in families affected by Duchenne muscular dystrophy, and 23 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
0
24
1
Order By: Relevance
“…30,31,37,38,42 Beneficial influences also were observed, including high reported satisfaction among tested children and positive emotional responses among children who tested negative. 30,31,34,36,37,39,42 Implications for future research Although this review suggests that a majority of publications do not indicate a substantial impact of genetic testing on children's psychosocial wellbeing, most position statements recommend against the testing of children. 1,2 This difference is likely because of the serious limitations of the current evidence and a tendency of health care organizations to take a precautionary stance with respect to potential harms, 49 particularly when children are involved.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…30,31,37,38,42 Beneficial influences also were observed, including high reported satisfaction among tested children and positive emotional responses among children who tested negative. 30,31,34,36,37,39,42 Implications for future research Although this review suggests that a majority of publications do not indicate a substantial impact of genetic testing on children's psychosocial wellbeing, most position statements recommend against the testing of children. 1,2 This difference is likely because of the serious limitations of the current evidence and a tendency of health care organizations to take a precautionary stance with respect to potential harms, 49 particularly when children are involved.…”
Section: Discussionmentioning
confidence: 96%
“…36 Finally, retrospective reports indicated that most children were generally content with their overall experience of having undergone carrier testing. High proportions of tested children answered affirmatively when a single item question was used to ask whether they were satisfied with testing (90 -100%), 30,31,34 completely satisfied with testing (76%), 39 either satisfied or very satisfied (91%), 35 would be tested again (85-100%), 34,39 and would recommend testing to a friend (76 -89%). 31,34,39 However, these measures could be subject to social desirability bias or, given the retrospective designs, optimistic recall bias.…”
Section: Carrier Testingmentioning
confidence: 99%
“…16 The second part had questions about satisfaction with the carrier testing and decisionmaking. 22 For the present study, we analyzed answers relating to awareness of the test result and the social and psychological significance of reception of the genetic carrier test result. As only a few fathers replied, and it was obvious that the mothers sometimes had also filled in the questionnaires of the fathers, fathers' replies were not analyzed.…”
Section: Gathering Informationmentioning
confidence: 99%
“…Järvinen et al, surveyed young adult women with a family history of Duchenne muscular dystrophy and hemophilia A. They reported that the majority of subjects believed that carrier testing should occur during childhood or teen-age years [13]. …”
Section: Aspects Of Graduated Autonomymentioning
confidence: 99%